Development of a cognitive bias methodology for measuring low mood in chimpanzees - Bateson,Melissa; Nettle,Daniel (PeerJ PrePrints, 2015)
There is an ethical and scientific need for objective, well-validated measures of low mood in captive chimpanzees. We describe the development of a novel cognitive task designed to measure ‘pessimistic’ bias in judgments of expectation of reward, a cognitive marker of low mood previously validated in a wide range of species, and report training and test data from three common chimpanzees (Pan troglodytes). The chimpanzees were trained on an arbitrary visual discrimination in which lifting a pale grey paper cone was associated with reinforcement with a peanut, whereas lifting a dark grey cone was associated with no reward. The discrimination was trained by sequentially presenting the two cone types until significant differences in latency to touch the cone types emerged, and was confirmed by simultaneously presenting both cone types in choice trials. Subjects were subsequently tested on their latency to touch unrewarded cones of three intermediate shades of grey not previously seen. Pessimism was indicated by the similarity between the latency to touch intermediate cones and the latency to touch the trained, unreinforced, dark grey cones. Three subjects completed training and testing, two adult males and one adult female. All subjects learnt the discrimination (107-240 trials), and retained it during five sessions of testing. There was no evidence that latencies to lift intermediate cones increased over testing, as would have occurred if subjects learnt that these were never rewarded, suggesting that the task could be used for repeated testing of individual animals. There was a significant difference between subjects in their relative latencies to touch intermediate cones (pessimism index) that emerged following the second test session, and was not changed by the addition of further data. The most dominant male subject was least pessimistic, and the female most pessimistic. We argue that the task has the potential to be used to assess longitudinal changes in sub-clinical levels of low mood in chimpanzees, however further work with a larger sample of animals is required to validate this claim.
Keywords: cognitive bias; judgment bias; affective state; chimpanzee; depression; animal welfare; psychopathology